Socialization of The Use of E-Books to Improve Students' Digital Literacy : Penelitian - Joice Soraya (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
During contemplation and discussions with fellow academics and teaching staff, the author came up with a solution to create an e-book and disseminate it to senior high school students at State Senior High School 1, Malang City, East Java, Indonesia, over three days. This socialization was conducted for three days at the State Senior High School of Malang, East Java, Indonesia. This socialization was carried out based on the low digital literacy of students in the city of Malang and the low level of student interest in Physical Books. Therefore, the author took the initiative to create an e-book about "How to Use Social Media Well," "Learning to Be Brave with Conscience," and "Work Hard, Work Smart, and Work Sincerely." The presence of this e-book, the author hopes, can improve students' digital literacy and increase students' interest in scientific work, one of which is e-books.